2011
DOI: 10.1371/journal.pone.0016521
|View full text |Cite
|
Sign up to set email alerts
|

Recipient Outcomes after ABO-Incompatible Liver Transplantation: A Systematic Review and Meta-Analysis

Abstract: BackgroundABO-incompatible live transplantation (ILT) is not occasionally performed due to a relative high risk of graft failure. Knowledge of both graft and patient survival rate after ILT is essential for donor selection and therapeutic strategy. We systematically reviewed studies containing outcomes after ILT compared to that after ABO-compatible liver transplantation (CLT).Methodology/Principal FindingsWe carried out a comprehensive search strategy on MEDLINE (1966–July 2010), EMBASE (1980–July 2010), Bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 38 publications
2
50
1
1
Order By: Relevance
“…It has been reported that ABO-mismatch recipients have a higher risk of acute rejection (32). In the present study, 2 out of 6 recipients with ABO-incompatible liver grafts developed acute rejection.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been reported that ABO-mismatch recipients have a higher risk of acute rejection (32). In the present study, 2 out of 6 recipients with ABO-incompatible liver grafts developed acute rejection.…”
Section: Discussionsupporting
confidence: 50%
“…However, it has been said that the outcome of LDLT performed for patients with acute liver failure, including fulminant hepatitis, is good (32). Among the 47 patients enrolled in the present study, there were only 4 with acute liver failure.…”
Section: Discussionmentioning
confidence: 75%
“…Since the introduction of desensitization (DSZ) with the anti-CD20 monoclonal antibody rituximab (RIT), the risk of hepatic necrosis caused by full-blown AMR has almost disappeared, and overimmunosuppression aimed at avoiding AMR is no longer required (5,6). Nonetheless, most reports on the clinical outcomes of ABOi ALDLT in the literature still include unfavorable outcome data from before the RIT era, leading to overestimation of the morbidity rate and underestimation of the survival rate of current ABOi ALDLT (7). As such, misconceptions about unacceptable clinical outcomes of ABOi ALDLT persist and limit the widespread application of ABOi ALDLT.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic artery thrombosis occurred in 24% of ABOi allografts [3,28]. The metaanalysis of Wu et al [2] in 2011 showed the total complication incidence and acute rejection incidence to be higher after ABOi LDLT than after ABOc LT. Lee at al. [23] performed ABOi LDLT with a protocol of plasmapheresis, IVIG, and quadruple immunosuppressive therapy (basiliximab, tacrolimus, mycophenolate mofetil, steroids).…”
Section: Discussionmentioning
confidence: 99%